Monocyte response in myocardial infarction in patients with type 2 diabetes - G. A. Kukharchik; O. K. Lebedeva; L. B. Gaykova (Российский кардиологический журнал)
Aim. To reveal the features of monocyte response in myocardial infarction (MI) in patients with type 2 diabetes (T2D).Material and methods. The study included 121 patients with MI and T2D as follows: 76 — with target glycated hemoglobin (HbA1c), 45 — with elevated HbA1c values. In addition to the standard examination, all patients underwent a blood test for HbA1c on day 1 of MI, while on days 1, 3, 5, and 12±1, monocyte subpopulations were assessed by flow cytometry.Results. Patients with target HbA1c were older than patients with elevated HbA1c levels. In the group with target HbA1c, the number of CD16(+) monocytes on the 1st day of MI was significantly higher: 61,38 (39,2; 100,08) cells/µl vs 35,7 (28,98; 40,33) cells/µl, p=0,03; on the 3rd day of MI, the number of "intermediate" CD14(+)CD16(+) monocytes was higher: 74,82 (71,78; 83,2) cells/µl vs 25,90 (14,04; 57,12) cells/µl, p=0,03, while the CD16(-) to CD16(+) monocyte ratio on the 3rd day of MI was lower: 8,32 (6 ,87; 10,03) vs 10,81 (8,90; 21,10), p=0,04. At the same time, in the group of patients with target HbA1c values, the level of CD16(+) monocytes on the 3rd day of MI was significantly higher in patients aged <71 years compared with patients ≥71 years: 104,55 (63,64; 149,7) cells/µl vs 55,20 (36,92; 76,59) cells/µl, p=0,03.Conclusion. In patients with T2D and target HbA1c values, compared with patients with elevated HbA1c, the inflammatory response in MI is associated with higher levels of CD16(+) monocytes on days 1 and 3 of MI, which is more typical for people aged <71 years.